Dscam1 in Pancrustacean Immunity: Current Status and a Look to the Future - Armitage, Sophie A. O.; Kurtz, Joachim; Brites, Daniela; Dong, Yuemei; Du Pasquier, Louis; Wang, Han-Ching (Frontiers in Immunology, 2017)
The Down syndrome cell adhesion molecule 1 (Dscam1) gene is an extraordinary example of diversity: by combining alternatively spliced exons, thousands of isoforms can be produced from just one gene. So far, such diversity in this gene has only been found in insects and crustaceans, and its essential part in neural wiring has been well-characterised for Drosophila melanogaster. Ten years ago evidence from D. melanogaster showed that the Dscam1 gene is involved in insect immune defence, and work on Anopheles gambiae indicated that it is a hypervariable immune receptor. These exciting findings showed that via processes of somatic diversification insects have the possibility to produce unexpected immune molecule diversity, and it was hypothesised that Dscam1 could provide the mechanistic underpinnings of specific immune responses. Since these first publications the quest to understand the function of this gene has uncovered fascinating insights from insects and crustaceans. However, we are still far from a complete understanding of how Dscam1 functions in relation to parasites and pathogens and its full relevance for the immune system. In this Hypothesis and Theory article we first briefly introduce Dscam1 and what we know so far about how it might function in immunity. By focussing on seven questions, we then share our sometimes contrasting thoughts on what the evidence tells us so far, what essential experiments remain to be done, and the future prospects, with the aim to provide a multi-angled view on what this fascinating gene has to do with immune defence.